Pain Reduction from Dysmenorrhea Using a Warm Compress and Lavender Aromatherapy - Yeti Trisnawati; Nining Sulistyowati (International Journal of Public Health Excellence (IJPHE), 2022)
Cases of dysmenorrhea are quite high among college students, ranging from 53% to 86%. If this problem is not resolved immediately, it will have an impact on decreasing learning activities, social activities and student learning achievements. One of the non-pharmacological treatments that can be done alone is with warm compresses and lavender aromatherapy. The purpose of this study was to determine the effectiveness of warm compress and lavender aromatherapy to reduce dysmenorrhea. This pre-experimental study involved two groups (warm compress group and the lavender aromatherapy group) with purposive sampling. The number of samples is 30 respondents. Pain is measured by Numeric Rating Scale (NRS). Statistical test with paired sample t-test and independent t-test. The results showed that there was a decrease in the dysmenorrhea pain scale after intervention. In the warm compress group it decreased from 4.00 to 2.93 (p = 0.001). In the lavender aromatherapy group, from a scale of 3.40 to 2.60 (p=0.001). From the results of the difference in the effect of warm compresses and lavender aromatherapy, it shows a p-value of 0.575, Its means can be said that warm compresses and lavender aromatherapy are both effective. in reducing dysmenorrhea